From Slater to Mott physics by epitaxially engineering electronic correlations in oxide interfaces - Carla Lupo (Nature Portfolio, 2021)
Abstract Using spin-assisted ab initio random structure searches, we explore an exhaustive quantum phase diagram of archetypal interfaced Mott insulators, i.e. lanthanum-iron and lanthanum-titanium oxides. In particular, we report that the charge transfer induced by the interfacial electronic reconstruction stabilises a high-spin ferrous Fe2+ state. We provide a pathway to control the strength of correlation in this electronic state by tuning the epitaxial strain, yielding a manifold of quantum electronic phases, i.e. Mott-Hubbard, charge transfer and Slater insulating states. Furthermore, we report that the electronic correlations are closely related to the structural oxygen octahedral rotations, whose control is able to stabilise the low-spin state of Fe2+ at low pressure previously observed only under the extreme high pressure conditions in the Earth’s lower mantle. Thus, we provide avenues for magnetic switching via THz radiations which have crucial implications for next generation of spintronics technologies.